1995
DOI: 10.1159/000111289
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Complexes of the Electron Transport Chain in Synaptic Mitochondria from Rat Brain

Abstract: The postnatal development of the complexes of the electron transport chain in mitochondria isolated from rat brain synaptosomes was investigated. Synaptosomal brain mitochondria were isolated from rats aged 10–60 days, and the activities of mitochondrial complex I, complex Il-III, complex IV and complex V were measured. There was a significant increase in the activity of complex V from day 10 to day 60 post partum, and in the activities of complex II-III from day 10 to day 15 and complex IV from day 10 to day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
4
20
1
Order By: Relevance
“…Diverse developmental patterns of mitochondrial activity during post-natal brain development, however, also have been reported. For example, it has been reported complex I activity does not change during postnatal development, complex IV activity peaks a p20, and complex V activity increases linearly from p10 to p60 in the brain (Almeida et al 1995). These complex developmental patterns have also been previously reported for the expression of similar functional mitochondrial proteins.…”
Section: Genome Research 1381supporting
confidence: 63%
See 1 more Smart Citation
“…Diverse developmental patterns of mitochondrial activity during post-natal brain development, however, also have been reported. For example, it has been reported complex I activity does not change during postnatal development, complex IV activity peaks a p20, and complex V activity increases linearly from p10 to p60 in the brain (Almeida et al 1995). These complex developmental patterns have also been previously reported for the expression of similar functional mitochondrial proteins.…”
Section: Genome Research 1381supporting
confidence: 63%
“…It has been shown that an increase in activity of mitochondrial enzymes does occur during postnatal development (Szutowicz et al 1982;Bukato et al 1992;Almeida et al 1995). Although enzyme activity and expression do not necessarily correspond, we observed significant increases in the expression of mitochondrial proteins from p1 to p45 that correspond to reports on enzyme activity.…”
Section: Genome Research 1381supporting
confidence: 51%
“…In this study, complex I in the synaptosomal mitochondria was inhibited by only ϳ10% before a decrease in oxygen consumption was observed, which is more in accordance with the level calculated for synaptic mitochondria, as would be expected, because a similar sample of mitochondria exists in isolated synaptic mitochondria preparations as in the synaptosomal preparations. A previous study showed that complex I activity was 36% lower in synaptic mitochondria than in nonsynaptic mitochondria (25), which may somewhat explain the lower thresholds obtained in synaptic and synaptosomal mitochondria when compared with nonsynaptic mitochondria. Similarly, a recent study found that complex I activity in C57BL/6J mouse brain synaptic mitochondria was 45% lower than that in nonsynaptic mitochondria (26).…”
Section: E (Error Bars)mentioning
confidence: 87%
“…Second, as energy demand and oxygen consumption increase postnatally, the activities of many mitochondrial enzymes involved in energy metabolism are gradually increased (Kalous, et al, 2001). These enzymes include adenine nucleotide translocase (Schonfeld and Bohnensack, 1995), creatine kinase (Holtzman, et al, 1993, Schonfeld andReiser, 2007), malic enzyme (Bukato, et al, 1992), the pyruvate dehydrogenase complex (Malloch, et al, 1986), the electron transport chain complexes (Almeida, et al, 1995, Bates, et al, 1994, Krebs cycle enzymes (Clark, et al, 1981, Leong and, glutamate dehydrogenase , as well as antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase (Mavelli, et al, 1982). To our knowledge, however, changes in rat brain DLDH expression and activity during postnatal development have not been reported.…”
Section: Introductionmentioning
confidence: 99%